MANAGEMENT PRACTICES OF THE FARMERS REARING JERSEY X SAHIWAL COWS IN CHITTOOR DISTRICT OF ANDHRA PRADESH - VARAPRASAD, A. REDDY; RAGHUNANDAN, T.; KUMAR, M. KISHAN; PRAKASH, M. GNANA (Indian Journal of Animal Production and Management, 2017)
ABSTRACTThe study on the managerial practices followed by the farmers rearing Jersey x Sahiwalcows revealed that 25.8 and 56.3 per cent of the farmers were feeding green fodder adlibitum and in limited quantity, respectively. Majority of the farmers i.e. 77.4 per cent werefeeding dry fodder ad libitum. Only 5.3 per cent farmers were feeding optimum level ofconcentrate feed while majority of the farmers (81 per cent) were feeding restricted concentratefeed. Regular feeding of mineral mixture was practiced by 63.7 per cent of the farmers. All thefarmers were aware of heat detection in cows and Artificial Insemination. Present study revealedthat on an average, 2.43 inseminations were required for each conception. Most of thefarmers(91.68) provided kutcha housing to animals while 27.9 per cent farmers had manure disposalpits. Average hygiene levels were observed in most of the cases. All the dairy farmers allowedsuckling by their calves before and after milking and followed full hand milking twice a dayregularly. Weaning of calves was not followed. Mastitis was the major health problem faced bythe farmers followed by theileriasis and FMD. Prevalent reproductive problems were repeatbreeding, anoestrus and retained placenta. Most of the farmers (89%) were vaccinating theanimals by the vaccines provided by AnimalHusbandry Department and none of the farmers was following recommended vaccination anddeworming schedule.Key words : Jersey x Sahiwal cows, Managerial practices, Farmers, Chittoor, Andhra Pradesh